2008
DOI: 10.1021/bi800722d
|View full text |Cite
|
Sign up to set email alerts
|

Helix Mutations Stabilize a Late Productive Intermediate on the Folding Pathway of Ubiquitin

Abstract: We have investigated the relative placement of rate-limiting energy barriers and the role of productive or obstructive intermediates on the folding pathway of yeast wild-type ubiquitin ( wt-Ub) containing the F45W mutation. To manipulate the folding barriers, we have designed a family of mutants in which stabilizing substitutions have been introduced incrementally on the solvent-exposed surface of the main alpha-helix (residues 23-34), which has a low intrinsic helical propensity in the native sequence. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…These data demonstrate that this α-helix might stabilize the NOD tertiary structure. The result supports the model suggested above, since the α-helix was shown to be the crucial element in the formation of the ubiquitin-fold [41], [42].…”
Section: Resultssupporting
confidence: 90%
“…These data demonstrate that this α-helix might stabilize the NOD tertiary structure. The result supports the model suggested above, since the α-helix was shown to be the crucial element in the formation of the ubiquitin-fold [41], [42].…”
Section: Resultssupporting
confidence: 90%
“…We also observed a pronounced rollover in the refolding data for the IfN transition which has an initially positive slope for m IN in contrast to the denaturant-independent initial rate profile for k IN observed for FN and WN (m IN e 0) (Figure 7b). This suggested that the intermediate was required to partially unfold to reach the rate-limiting transition state, consistent with a highly compact and misfolded species (27,28). We do not, however, observe the additional refolding and unfolding phases for L8W that are indicative of the more complex kinetics identified for WN.…”
Section: T H I S C O N T E N T Imentioning
confidence: 52%
“…We also considered whether the complex kinetics observed for the WN mutant could be reproduced in the wt-Ub sequence within the context of the native G-bulged type I turn by introducing the L8W mutation in to wt-Ub (TLTGKfTWTGK) (28). This resulted in a highly fluorescent protein that similarly underwent a large change in fluorescence intensity upon folding.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we investigate the thermodynamics and kinetics of Ub folding, which has been investigated by a variety of experiments and computations. , However, the effects of denaturants, such as guanidinium chloride and urea, have not been considered in simulations. This is important because there are few central experimental controversies, such as the extent of collapse in the denatured ensemble of Ub as the denaturant concentration is lowered and if intermediates are present, that remain unresolved.…”
Section: Introductionmentioning
confidence: 99%